The signature of the western boundary currents on tropospheric climate variability - Larson, James, author; Hurrell, James, advisor; Thompson, David, advisor; Willis, Megan D., committee member (Colorado State University. Libraries, 2024)
Oceanic western boundary currents play a crucial role in transporting heat poleward, thereby influencing the midlatitude climatological-mean climate and serving as an important role for midlatitude storm tracks that provide rainfall to land regions. It is not yet firmly established what role these oceanic currents play in influencing atmospheric variability. Characterized by the presence of mesoscale features such as oceanic eddies and sharp sea surface temperature (SST) gradients, the western boundary currents define a uniquely separate regime for air-sea interactions on climatic timescales relative to the rest of the ocean basins. In this study, simple but robust observational and modeling evidence reveals that anomalous precipitation and vertical motion co-vary with local SST anomalies in the western boundary currents, with a measurable influence extending into the upper troposphere. Periods of anomalously warm SSTs are associated with anomalous, co-located upward motion of > 0.02 Pa/s and precipitation anomalies of ~0.6 mm/day when averaged over a month. Yet, the standard resolution of most climate models, with grid cells on the order of 100 kilometers, fail to capture this co-variability. It is demonstrated that sharpening the horizontal resolution in both a climate model and in atmospheric reanalyses alters the spatial patterns both of sea surface temperature and of regional atmospheric processes. Given the significant influence of these western boundary currents on the broader regions surrounding them, climate projections conducted with grid cells coarser than 50 kilometers may overlook crucial processes.
Keywords: atmospheric dynamics; climate variability; climate dynamics; air-sea interactions